Engineering Students perceptions on Learner Autonomy: a mixed methodology approach - Duarte, M. (2018)
Student-centered learning requires students taking responsibility for their own learning, and becoming autonomous learners. Using a mixed methodology approach with a sequential explanatory design, this paper reports some results from an ongoing research about learner autonomy of mechanical engineering students (first cycle) in Portugal. For the purpose of this paper, the focus is the relationship between learner autonomy and academic achievement and the way it translates to students’ perceptions of autonomy in learning, its characteristics and importance, and how having students talk about learner autonomy can be useful to improve their learning and build a bridge between research and practice in Engineering Education. The results show that students have positive perceptions about their own learner autonomy and its importance. A positive moderated statistically significant correlation was found between learner autonomy and academic achievement, which is mainly due to the control dimension of learner autonomy. Students lack initiative, with this dimension being the one that least contributes to learner autonomy, and having no statistically significant correlation with academic achievement. Because of this, promoting actions that increase students taking initiative seems to be a way of improving learner autonomy. However, the actions taken have to consider that for some students, learner autonomy requires perseverance and is difficult to maintain. So, even though for most students, having opportunities to improve may be enough, less autonomous students may require that the action of teachers and the curricular activities proposed, promotes an academic environment that encourages and supports autonomy in learning.